REPRESENTASI BUDAYA BATAK TOBA DALAM FILM TOBA DREAMS - Fauzan Arif Baren Fandi; Belli Nasution (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This Study aimed to analyze the semiotic meaning about cultural of Batak Toba in ToBa Dreams film with researching the dennotative meaning, connotative meaning, and Myth/Ideology according to Roland Barthes’s. In addition, this study also aimed to find out how the Batak Toba Culture is represented through the ToBa Dreams Film.The method of this study is a qualitative research. The technique of collecting data is using documentation study, observation study, library study, and online data search. The object to analyse is the scenes in ToBa Dreams film as much as five scenes.The result of this study showed that there are three meanings according to Roland Barthes’s semiotic, dennotative meaning that seen in the scenes of ToBa Dreams is representating Batak Toba through the actors/actress, literal meaning from dialogues, nature condition, Tourist attraction at Toba Lake, and monuments of the custom home and typical graves of Batak Toba. Connotative meaning in this film is formed by action of characters, the meaning of speech based on the meaning implied in the dialogue that conveyed depict the values, customs, kinship relations, moral messages, and the belief system of Batak Toba society is dominant with the teachings of Christians. The meaning of myth / ideology contained in several scenes is interpreted through literature study about batak culture that understand custom values, patrinilial system, customs, and tolerance among religious people who have became a culture among the Batak Toba people.Keywords: representation, film, toba dreams, semiotic